Penerapan Model Pembelajaran Numbered Head Together dalam Meningkatkan Keterampilan Komunikasi dan Hasil Belajar Siswa SMK Swasta Kristen Tomosa 1 Tahun Pelajaran 2024/2025 - Adika Zai (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
The low level of students’ communication skills and learning outcomes in science learning remained a major problem in the teaching and learning process at secondary schools. This condition was reflected in the lack of students’ active participation, the dominance of conventional teaching methods, and students’ low confidence in expressing opinions during classroom activities. This study aimed to improve students’ communication skills and learning outcomes through the implementation of the Numbered Head Together (NHT) learning model at SMK Swasta Kristen Tomosa 1 in the 2024/2025 academic year. The study employed a Classroom Action Research (CAR) approach conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 30 students of class X-TKJ. Data were collected through observation, questionnaires, interviews, documentation, communication skills rubrics, and learning achievement tests. The findings revealed that the implementation of the Numbered Head Together model improved the quality of learning from 68% to 92%, students’ communication skills from 68% to 92%, and students’ learning outcomes from an average score of 63.94 to 86.23 with a learning mastery level reaching 90%. These findings indicated that the Numbered Head Together model was effective in enhancing active participation, communication skills, and students’ learning outcomes in science learning.